Financial Performance Analysis on Financial Distress in ASEAN Six - Masripah; Arieftiara, Dianwicaksih (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to analyze the influence of financial ratios on the likelihood of financial distress in property and real estate companies listed on the stock exchanges of six ASEAN countries, namely Indonesia, Malaysia, Thailand, Singapore, the Philippines, and Vietnam during the period 2018–2022. The variables analyzed include Total Asset Turnover, Sales Growth, Current Ratio, Debt Ratio, and Return on Investment. The method used is a quantitative approach with logistic regression, based on 1,630 firm-year observations obtained from the company's financial statements. The results of the Hosmer and Lemeshow test indicate that the initial model is not appropriate, but alternative tests through the Area Under the Curve value of 0.7728 indicate that the model has quite good predictive ability. The analysis results show that Sales Growth and Current Ratio have a significant negative effect on financial distress, while Debt Ratio has a significant positive effect. Conversely, Total Asset Turnover and Return on Investment do not show a significant effect. These findings emphasize the importance of considering aspects of liquidity, sales growth, and capital structure in predicting financial risk, especially in the property sector which has long-term investment characteristics. This research contributes to broadening the understanding of cross-border financial risk in the ASEAN region.